(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This literature review aims at exploring two career theories, one career model, and their applications to facilitate the comparison of their advantages and shortcomings in understanding contextual and personal factors influencing teachers’ career choices. It first examines the chosen career theories and models in teachers’ professional development, namely, Fuller’s Concern Stage Theory, Fessler’s Eight-stage Teacher Career Cycle Model The Social Cognitive Career Theory. Through a discussion of those teachers’ career theories, models and their applications, this literature review probes into the importance of examining the interplay between personal and environmental factors in order to understand how and why experienced teachers become demotivated and frustrated in different career stages. It also provides a more holistic view and insight on retaining experienced in-service teachers and alleviating the global teacher attrition and shortage problem.